THE IMPACT OF MODERATION OF PRICE DISCOUNTS: BRAND IMAGE AND E-WOM ON PURCHASE DECISIONS - Fikriyah, Nur Laili; Baiturrohman, Baiturrohman; Nur Afifah, Yans (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2024)
This study aims to examine the influence of brand image and electronic Word of Mouth (E-WOM) on purchasing decisions, and the moderating influence of price discount variables. This study uses a quantitative approach with a survey method on Shopee-food Mie Gacoan consumers aged 18-35 years. The sampling technique used purposive sampling with a total of 230 respondents. In this study, data was managed and analyzed using the Smart-PLS 3.0 application. The tests carried out were validity and reliability tests, model suitability tests, and hypothesis tests. The results of this study are that brand image has a significant influence on purchasing decisions. Electronic Word of Mouth (E-WOM) has a significant influence on purchasing decisions. The next result is that price discounts do not moderate brand image and Electronic Word of Mouth (E-WOM) on purchasing decisions. In line with previous studies, price discounts do not have a significant moderating influence on purchasing decisions. Based on the results of this study, it shows that it is in line with previous studies and provides additional references for further research.